Mapping the landscape of ICTs in agriculture research: a bibliometric analysis of influential publications and authors - Abdullahi, Husein Osman; Mahmud, Murni; Hassan, Abdikarim Abi; Ali, Abdifatah Farah (Success Culture Press, 2023)
This study aims to identify influential publications and authors in the field of ICTs in agriculture research through a bibliometric analysis. A search on the SCOPUS database yielded 1,104 documents published between 2010 and 2023, from which the 100 most-cited articles were determined. VOSviewer was employed for bibliometric analyses, including keyword occurrences, co-authorship networks, and bibliometric coupling networks. The analysis revealed that India, the UK, and the USA had the highest number of publications, while contributions from Africa were limited. Key recurring keywords included ICT, agriculture, information and communication, information management, and sustainable development. High-ranked journals with significant impact were identified, emphasizing the importance of journal metrics. The study highlighted the potential of ICT in enhancing agricultural performance, productivity, food security, farmer livelihoods, and stakeholder awareness. Despite limitations such as relying on a single database (SCOPUS) and focusing on highly cited publications, this bibliometric analysis provides valuable insights into ICTs in agriculture research. To enrich future research, it is recommended to incorporate multiple databases and consider a broader range of publications. Furthermore, given the limited number of existing bibliometric studies in ICT in agriculture, further research is warranted to advance knowledge in this area.